2018
DOI: 10.1016/j.ijbiomac.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of starches from Arracacha (Arracacia xanthorrhiza) roots

Abstract: Arracacha (Arracacia xanthorrhiza Bancroft) is an underexplored Andean root with a high starch content. In this work, starches from two different varieties of Peruvian arracacha were evaluated and characterized in relation to their granule morphology, molecular structure and properties. The starches presented round or polygonal shapes, with a mean diameter of ~20 μm and B-type granules. They were rich in amylopectin molecules with long chain lengths (with the ability to complex iodine) and some with intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…ZM8229 showed the highest WAC, compared with the other cassava starches, indicating that ZM8229 had the best ability to bind water. The WAC was similar to that reported by Bergel, Da Luz and Santana [32] and Nanci et al [33] According to Falade and Okafor [34] , the differences in the water absorption capacities among the germplasms may be attributed to differences in the amylose content and amylopectin. The water absorption of starch was reported to be essentially a characteristic of amylopectin components.…”
Section: Water and Oil Absorption Capacitiessupporting
confidence: 89%
See 1 more Smart Citation
“…ZM8229 showed the highest WAC, compared with the other cassava starches, indicating that ZM8229 had the best ability to bind water. The WAC was similar to that reported by Bergel, Da Luz and Santana [32] and Nanci et al [33] According to Falade and Okafor [34] , the differences in the water absorption capacities among the germplasms may be attributed to differences in the amylose content and amylopectin. The water absorption of starch was reported to be essentially a characteristic of amylopectin components.…”
Section: Water and Oil Absorption Capacitiessupporting
confidence: 89%
“…ZM8229 had the highest transparency, followed by 6068 (16.10%) and SC9 (14.93%), whereas 274 exhibited the lowest transparency level. Achille et al [36] , Nwokocha [37] and Nanci et al [33] reported transparencies of 40.7%, 20.0% and 90% for cassava starches for a 1% starch paste at 650 nm, which were significantly higher than the results of this study. This difference may have been due to the variation in the granule size [38,39] and amylose content.…”
Section: Water and Oil Absorption Capacitiescontrasting
confidence: 80%
“…Considering the solubility results at 50 °C, which, according Castanha et al (2018) is slightly higher than the onset temperature of the samples, it was possible to observe the higher values of solubility, which can be explained by the amylose fractions that may have leached from the granules at this temperature [29]. At 70 °C, all water available for gelatinization was entirely absorbed by the granules, and there was no soluble part to evaluate.…”
Section: Swelling Power and Solubilitymentioning
confidence: 83%
“…Arracacha or Peruvian carrot ( Arracacia xanthorriza ) is a native tuber of the Andean region in South America in countries, like Colombia, Peru, Bolivia, and Ecuador ( Castanha et al., 2018 ; Londoño-Restrepo et al., 2018 ; Lovera et al., 2017 ). Traditionally, Arracacha ranks among the main carbohydrate sources in said countries, alongside potatoes, plantains, and cassava due to its traditional use in culinary dishes( dos Santos et al., 2018 ; Gutiérrez Malaxechebarría, 2011 ; Moraes et al., 2014 ; Rocha et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest in Arracacha has increased, especially in Colombia where crops have grown considerably, however, it is still and underused product, that could have many applications in different areas of the food industry ( Gutiérrez Malaxechebarría, 2011 ). Likewise, there is a growing interest i in the food industry for new starch sources, such as Andean tubers, which can be used as food ingredients and additives ( Castanha et al., 2018 ; Cisneros et al., 2009 ; Cruz et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%